Antioxidant activity, anthocyanin profile, and mineral compositions of colored wheats - Shamanin, Vladamir P.; Tekin-Cakmak, Zeynep Hazal; Karasu, Salih; Pototskaya, Inna, V; Gordeeva, Elena I.; Verner, Artem O.; Morgounov, Alexey I.; Yaman, Mustafa; Sagdic, Osman; Koksel, Hamit (CODON PUBLICATIONS, 2024)
The antioxidant activities (ABTS and CUPRAC) of 40 different colored wheat genotypes were investigated, and some of the diverse wheat genotypes were selected to investigate their anthocyanin profiles and mineral compositions. The ABTS values of free and bound fractions were in the range of 15.61-157.36 mg TE/100 g and 33.26-189.48 mg TE/100 g, respectively. For the free and bound fractions of the colored wheat samples, the CUPRAC values were determined between 25.73 and 229.20 mg TE/100 g, and between 82.00 and 348.93 mg TE/100 g, respectively. The anthocyanin profiles of the colored wheats varied depending on the genotypes. Cyanidin-3-O-glucoside chloride was abundant in the samples w3, w8, w17, w18 and w20 while malvidin-3O-glucoside chloride was the major anthocyanin for the samples w13, w23, w14, w30 and w34. Cyanidin-3-Oglucoside chloride was significantly higher in w18 than others (p<0.05). Cyanidin-3,5-di-O-glucoside was only found in the free extracts of the two samples (w17 and w20). The best accessions with high antioxidant activity and anthocyanin profile were identified for their potential utilization in wheat breeding programs. According to the results, the w17 sample (line BW 49880-Dark colored P, F4) was chosen as the best sample due to its highest antioxidant activity (p<0.05) and the best anthocyanin profile. The macronutrients Ca, K, and Mg highly varied among the genotypes studied. The trace elements, Zn and Fe were significantly higher in purple-grained lines than that of the red-grained variety. The study's outcomes are likely to support breeding programs to generate new wheat cultivars with greater nutritional benefits.
Keywords: ABTS; anthocyanin profile; colored wheats; CUPRAC; mineral compositions; PURPLE; BLUE; BLACK; L.; Food Science & Technology